Pharmacological management of cardio-renal-metabolic disease including new potassium binders. (March 2023) - Green, Darren; James, Benjamin; Hussain, Nehal
Abstract: Management of cardio-renal-metabolic diseases encompasses multiple therapeutic targets including heart failure, progression of chronic kidney disease, proteinuria, hypertension and glycaemic control. Limitations in optimizing pharmacological therapy in this setting are greatest for heart failure with reduced ejection fraction. Here, the concurrent use of all four major drug classes is seen in as few as a third of patients, with worsening renal function and hyperkalaemia being major barriers to optimization. These four main drug classes are discussed here in the context of strategies to optimize their use in heart failure, and also how their use in heart failure may need adjustment for co-morbid factors such as proteinuria, diabetes and hypertension. The drugs discussed are β-adrenoceptor blockers, angiotensin-converting enzyme inhibitors/angiotensin receptor blockers/angiotensin receptor–neprilysin inhibitors, mineralocorticoid receptor antagonists and sodium glucose co-transporter 2 inhibitors. Consideration is also given to the potassium binders sodium zirconium cyclosilicate and patiromer sorbitex calcium. These facilitate the use of therapies otherwise contraindicated by hyperkalaemia. As evident from recent European and US guidance, it is clear that a one-size-fits-all approach to cardio-renal-metabolic drug dosing is unfeasible. Cross-specialty multidisciplinary clinics may optimize polypharmacy delivery to patients with complex multiple long-term conditions.